Perspective of membrane distillation applied to ocean thermal energy conversion. Issue 1 (December 2015) - Kim, A. S.; Oh, W.; Lee, H.-S.; Cha, S.; Kim, H.-J.
Abstract : Authors investigated the potential application of vacuum membrane distillation (VMD) to the conventional ocean thermal energy conversion (OTEC). Open, closed, and hybrid cycles of OTEC are reviewed, and strategies to enhance performance of open cycle (OC) using VMD are discussed. The advantages of using VMD modular sets include reducing system sizes and enhancing power production rates. Our rough estimation indicates that VMD uses only about 10 per cent of the system volume required by OC-OTEC. Tasks to actualize the promising VMD technology are discussed for the next generation OC-OTEC.